Coral-based proxy calibrations constrain ENSO-driven sea surface temperature and salinity gradients in the Western Pacific Warm Pool - Mohtar, Ahmed T. (2021)
Constraining past variability in ocean conditions in the Western Pacific Warm Pool (WPWP) and examining how it has been influenced by the El-Niño Southern Oscillation (ENSO) is critical to predicting how these systems may change in the future. To characterize the spatiotemporal variability of the WPWP and ENSO during the past three decades, we analyzed climate proxies using coral cores sampled from Porites spp. from Kosrae Island (KOS) and Woleai Atoll (WOL) in the Federated States of Micronesia. Coral skeleton samples drilled along the major growth axis were analyzed for oxygen isotopes (δ18Oc) and trace element ratios (Sr/Ca), used to reconstruct sea surface salinity and temperature (SSS and SST). Pseudocoral δ18O time series (δ18Opseudo) were calculated from gridded instrumental observations and compared to δ18Oc, followed by fine-tuning using coral Sr/Ca and gridded SST, to produce age models for each coral. The thermal component of δ18Oc was removed using Sr/Ca for SST, to derive δ18O of seawater (δ18Osw), a proxy for SSS. The Sr/Ca, and δ18Osw records were compared to instrumental SST and SSS to test their fidelity as regional climate recorders. We found both sites display significant Sr/Ca-SST calibrations at monthly and interannual (dry season, wet season, mean annual) timescales. At each site, δ18Osw also exhibited significant calibrations to SSS across the same timescales. The difference between normalized dry season SST (Sr/Ca) anomalies from KOS and WOL generates a zonal SST gradient (KOSWOLSST), capturing the east-west WPWP migration observed during ENSO events. Similarly, the average of normalized dry season δ18Osw anomalies from both sites produces an SSS index (KOSWOLSSS) reflecting the regional hydrological changes. Both proxy indices, KOSWOLSST and KOSWOLSSS, are significantly correlated to regional ENSO indices. These calibration results highlight the potential for extending the climate record, revealing spatial hydrological gradients within the WPWP and ENSO variability back to the end of the Little Ice Age.